Climate Lawsuits and the Justiciability of the Right to a Clean and Healthy Environment: Trends in Judicial Practice in Indonesia - Silvester Magnus Loogman Palit; Tumian Lian Daya Purba; William Hendrik Reba (Westscience Press, 2026)
This study examines the development of climate litigation in Indonesia and its implications for the justiciability of the right to a clean and healthy environment. Using a normative legal approach, the research analyzes constitutional provisions, statutory regulations, and judicial decisions to evaluate how Indonesian courts interpret and enforce environmental rights in the context of climate change. The study finds that although the right to a clean and healthy environment is explicitly recognized in Article 28H(1) of the Constitution of the Republic of Indonesia 1945 and further supported by environmental legislation, its judicial enforcement remains inconsistent. Key challenges include limitations in legal standing, difficulties in establishing causation, and judicial reluctance to intervene in policy-related matters. Nevertheless, emerging judicial trends indicate a gradual shift toward more progressive interpretations, including the application of precautionary principles and broader recognition of environmental harm. This study concludes that strengthening legal frameworks, enhancing judicial capacity, and integrating climate-specific norms are essential to improving the enforceability of environmental rights. The findings contribute to the discourse on environmental constitutionalism and climate justice, particularly in developing country contexts.